2014
DOI: 10.2337/db14-0765
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Skeletal Muscle Mitochondrial ADP Recovery in Youth With Type 1 Diabetes Relates to Muscle Insulin Resistance

Abstract: Insulin resistance (IR) increases cardiovascular morbidity and is associated with mitochondrial dysfunction. IR is now recognized to be present in type 1 diabetes; however, its relationship with mitochondrial function is unknown. We determined the relationship between IR and muscle mitochondrial function in type 1 diabetes using the hyperinsulinemic-euglycemic clamp and 31P-MRS before, during, and after near-maximal isometric calf exercise. Volunteers included 21 nonobese adolescents with type 1 diabetes and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 36 publications
9
68
1
3
Order By: Relevance
“…In addition, we and others have documented decreased mitochondrial function and alterations in lipid metabolism in nondiabetic populations with IR, including burn trauma, aging, and HIV medication-related lipodystrophy (11,12,46). Most recently we found that the IR seen in type 1 diabetes, and insulinopenic state, is also related to mitochondrial dysfunction following exercise (10). Finally, defects in mitochondrial function and insulin signaling are even found in those individuals with a genetic risk for T2D prior to development of clinical hyperglycemia, indicating that mitochondrial alterations can be seen before clinical hyperglycemia, as in our participants (39).…”
Section: E728 Mitochondrial Function In Pediatric Hasmentioning
confidence: 56%
See 4 more Smart Citations
“…In addition, we and others have documented decreased mitochondrial function and alterations in lipid metabolism in nondiabetic populations with IR, including burn trauma, aging, and HIV medication-related lipodystrophy (11,12,46). Most recently we found that the IR seen in type 1 diabetes, and insulinopenic state, is also related to mitochondrial dysfunction following exercise (10). Finally, defects in mitochondrial function and insulin signaling are even found in those individuals with a genetic risk for T2D prior to development of clinical hyperglycemia, indicating that mitochondrial alterations can be seen before clinical hyperglycemia, as in our participants (39).…”
Section: E728 Mitochondrial Function In Pediatric Hasmentioning
confidence: 56%
“…In keeping with these findings, mitochondrial function has been shown to vary by sex (28). Many mitochondrial studies account for this by selecting to study one sex or balancing sex distribution within groups (10,27,53). However, in adults with vascular disease, once protein and muscle weight were corrected for, there were no differences in mitochondrial function per se (56).…”
Section: E729mentioning
confidence: 92%
See 3 more Smart Citations